Which is the larger issue in Indonesia: waste exports or imports? Interests in politics, economics, or the environment? - Solehudin, Rd. Heri (Revenue Journal: Management and Entrepreneurship, 2024)
The problem of waste management in Indonesia has become an urgent environmental issue, especially with the practice of importing waste from industrialized countries. This research aims to analyze the impact of waste imports in Indonesia from a political-ecological perspective, as well as social, economic and environmental dimensions. The method used is a literature review using the SLR 7P approach, collecting research data from the last five years. The research results show that waste imports in Indonesia are influenced by complex political and economic factors, including ego-sectoral interests which often ignore environmental and human welfare. Although the Basel Convention and national regulations aim to protect against the negative impacts of imported waste, their implementation is still less effective. This research also highlights the importance of a comprehensive evaluation of waste import policies in Indonesia and stricter law enforcement in dealing with violations.